The effect of supplementation perilla seeds (Perilla frutescens) in the diets on feed consumption and digestibility nutrients on ducks - Rendi Fathoni Hadi; Sudiyono; Zamzam Rizki Hamdani (Faculty of Animal Science, Universitas Brawijaya, 2022)
This study aims to determine the digestibility of perilla seeds (Perilla frutescens) in 3 levels (0, 2.5, and 5%) in rations given to local ducks. The research material used was male Mojosari ducks (Day Old Duck) with as many as 90 tails, with an average initial body weight of 35.36 grams. The ration consists of ground corn, pollard, fine bran, soybean meal (SBM), vitamin premix, and perilla seed supplementation. Livestock was separated by three treatments, P0: 100% basal ration without supplementation of Perilla frutescens L seeds; P1: 97.5% basal ration + 2.5% supplementation of Perilla frutescens L. seeds; P2: 95% basal ration + 5% supplementation of Perilla frutescens L. seeds. Duck ducks are kept for two months. The variables observed were crude protein digestibility, crude fat, crude fiber, and organic matter. The results showed a very significant effect (P <0.05) on the digestibility of crude protein, crude fat, and crude fiber and an insignificant effect (P> 0.05) on the digestibility of organic matter and feed consumption. Supplementation of perilla seeds can increase the digestibility of fat and fiber but decreases protein digestibility.